Guided skyrmion motion along pinning array interfaces - Vizarim, N. P. [UNESP]; Reichhardt, C.; Venegas, P. A. [UNESP]; Reichhardt, C. J.O. (Elsevier, 2021)
We examine ac driven skyrmions interacting with the interface between two different obstacle array structures. We consider drive amplitudes at which skyrmions in a bulk obstacle lattice undergo only localized motion and show that when an obstacle lattice interface is introduced, directed skyrmion transport can occur along the interface. The skyrmions can be guided by a straight interface and can also turn corners to follow the interface. For a square obstacle lattice embedded in a square pinning array with a different obstacle radius, we find that skyrmions can undergo transport in all four primary symmetry directions under the same fixed ac drive. We map where localized or translating motion occurs as a function of the ac driving parameters. Our results suggest a new method for controlling skyrmion motion based on transport along obstacle lattice interfaces.
Keywords: Edge transport; Ratchet effects; Skyrmion